A QUALITATIVE STUDY OF THE EXPERIENCE OF SOCIAL ISOLATION AND LONELINESS AMONG OLDER PEOPLE WITH CHRONIC DISEASES IN THE COMMUNITY - He, Mengfan; Wang, Peng (LIFE: International Journal of Health and Life-Sciences, 2024)
Social isolation and loneliness are major problems for older adults. Increasing evidence suggests that perceived social isolation or loneliness is associated with severe consequences for physical and mental health of older people with Chronic Diseases. This study aimed to investigate the experience of social isolation and loneliness among older adults with Chronic Diseases. This research was a descriptive qualitative study based on semi-structured face-to-face interviews. This study purposively selected community-dwelling older people with Chronic Diseases in Zhengzhou City, Henan Province, to explore older people’s experiences of social isolation and loneliness, the reasons why social isolation and loneliness occurs and the help they wish to receive. The qualitative content analysis was performed in order to summarize and extract themes from the interview texts. A total of 16 interviews were completed. Three themes were identified: 1) Inner emotions; 2)Reasons for social isolation and loneliness; 3)Desired assistance. It was found that social isolation and loneliness among older people with Chronic Diseases was not optimistic. Factors result in the social isolation and loneliness of older persons are manifold. Multidimensional intervention strategies should be adopted to alleviate the social isolation and loneliness of older people at the individual, family, community and social levels.